The emerging of employment gap in the Malaysian construction industry - Abdul Hamid, Abdul Rahim; Mohd Khazid, Nur Inayah; Yunus, Riduan; A Halim, Hazruwani; Abdul Razak, Amall Raihan (IOP Publishing, 2018)
Employment of young people is a big issue in the Malaysian construction industry. This is a common phenomenon not only in Malaysia but affected most developed and developing countries around the world. Sufficient workers are needed to cater to the robustness of the construction sector and to sustain the productivity that will boost the development demand. However, young people had difficulties to find decent employment in this industry due to lack of experience and skills among young people and some employer are more likely to hire foreign workers. The aim of this study is to examine the emerging of skill gaps in the Malaysian construction industry. The methodology adapted for this study comprise of primary and secondary data collection. The primary data had been collected from the questionnaire surveys on the professional within the construction industry. The data then were analyzed using the percentage score and the diagram such as bar chart had been used to visualize the results from the analysis. While, secondary data collected through literature review to gather information and important views from previous studies. The findings reveal that the construction industry prefer more than 30 years old skilled workers. Eventhough, the jobs could be filled by young people, but somehow, some barriers such as high risk, low wages, hard work and availability of foreign workers had distracted the involvement of young people in the construction industry.